Early Triassic Conchostracans (Crustacea: Branchiopoda) from the terrestrial Permian-Triassic boundary sections in the Moscow syncline - Scholze F.; Golubev V.; Niedźwiedzki G.; Sennikov A.; Schneider J.; Silantiev V. (2015)
© 2015 Elsevier B.V. The Permian-Triassic boundary marks the greatest mass extinction in Earth's history. In order to understand the real causes of this severe extinction event, multidisciplinary investigations around the globe are required. Here, the terrestrial Permian-Triassic boundary sections in the Vladimir region, Central Russia, were sampled bed-by-bed for conchostracan study. In the Early Triassic intervals the following taxa were recognized for the first time: Cornia germari (Beyrich, 1857), Euestheria gutta (Lutkevitch, 1937), Magniestheria mangaliensis (Jones, 1862), Palaeolimnadiopsis vilujensis Varentsov, 1955, and Rossolimnadiopsis Novozhilov, 1958. The wide distribution of C. germari demonstrates their high value for biostratigraphy, since this species was also reported from the Lower Buntsandstein Subgroup in the Germanic Basin as well as from Early Triassic deposits in Hungary, Greenland and Siberia. The assumption of an Early Triassic age of the studied sections is also supported by associated Tupilakosaurus bone fragments, which point to the Tupilakosaurus wetlugensis Zone in the earliest Triassic.